(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Postpartum Hemorrhage (PPH) is still among one of the most frequently occurring complications of childbirth that lead to severe suffering in the women following childbirth. This complication causes the highest percentage of maternal death in low resource countries due to inadequate access to emergency surgery. The risk of excessive bleeding is much more pronounced in cases of C-Sec when compared with natural birth, requiring complications-saving measures. To control blood loss Uterotonics like oxytocin and misoprostol are frequently used, but their usefulness is not always effective, particularly with atonic uterus and placental complications. The use of tranexamic acid (TXA), blood loss preventative surgical drugs, has gained popularity in recent years as it seeks to control intraoperative bleeding and lessen critical loss complications. Although it has proven efficiency in cases of trauma and non-obligatory surgery, there is little research on its pre-emptive use in C-Section. This study investigates the effectiveness of tranexamic acid on the amount of blood loss and its effects on maternal health indicators in women with high-risk pregnancies undergoing elective cesarean sections. Methodology: A randomized double-blind placebo controlled clinical trial was implemented at the obstetric ward of a tertiary care hospital. One hundred and fifty women with elective cesarean section were randomly distributed into two groups where one group received TXA infusion prior to the operation and one group served as a placebo. Blood loss was calculated intraoperatively with the use of a calibrated collection system, and hemoglobin levels were evaluated before the operation and after the operation. Other elements, such as blood transfusions, adverse events, maternal hemodynamic stability, and other hemodynamic stems, were also recorded. Results: The data showed that there was a statistically significant decrease in blood loss in the TXA group in comparison to the control group. Patients treated with TXA had lower rates of anemia and blood transfusions. There was no significant increase in thromboembolic complications or adverse reactions. Conclusion: These results bolster the safety profile of TXA for obstetric usage. The results highlight the potential use of TXA for increased effectiveness for blood loss during cesarean sections as well as for situations where blood transfusion resources are restricted. Incorporation of TXA into obstetric care routines would enhance maternal health indicators which reduces the pressure on medical resources. More research is needed to develop optimal dosing guidelines in order to validate the presumed long-term benefits of TXA on patients of varying demographics